Alkaloids in Chelidonium majus L: a review of its phytochemistry, pharmacology and toxicology - Li, Xin-Lan; Sun, Yan-Ping; Wang, Meng; Wang, Zhi-Bin; Kuang, Hai-Xue (Frontiers in Pharmacology, 2024)
Chelidonium majus L. (C. majus), commonly known as "Bai Qu Cai" in China, belongs to the genus Chelidonium of the Papaveraceae family. It has rich medicinal value, such as alleviating coughs, asthma, spasms and pain. Recent studies have demonstrated that C. majus is abundant in various alkaloids, which are the primary components of C. majus and have a range of pharmacological effects, including anti-microbial, anti-inflammatory, anti-viral, and anti-tumor effects. So far, 94 alkaloids have been isolated from C. majus, including benzophenanthridine, protoberberine, aporphine, protopine and other types of alkaloids. This paper aims to review the research progress in phytochemistry, pharmacology and toxicology of C. majus alkaloids, in order to provide a theoretical basis for the application of C. majus in the field of medicinal chemistry and to afford reference for further research and development efforts.